An Integrated Analysis of the Response of Colorectal Adenocarcinoma Caco-2 Cells to X-Ray Exposure - Guardamagna, Isabella; Lonati, Leonardo; Savio, Monica; Stivala, Lucia A.; Ottolenghi, Andrea; Baiocco, Giorgio (Frontiers in Oncology, 2021)
Colorectal cancer is among the three top cancer types for incidence and the second in terms of mortality, usually managed with surgery, chemotherapy and radiotherapy. In particular, radiotherapeutic concepts are crucial for the management of advanced rectal cancer, but patients’ survival remains poor, despite advances in treatment modalities. The use of well-characterized in vitro cell culture systems offers an important pre-clinical strategy to study mechanisms at the basis of cell response to therapeutic agents, including ionizing radiation, possibly leading to a better understanding of the in vivo response to the treatment. In this context, we present an integrated analysis of results obtained in an extensive measurement campaign of radiation effects on Caco-2 cells, derived from human colorectal adenocarcinoma. Cells were exposed to X-rays with doses up to 10 Gy from a radiotherapy accelerator. We measured a variety of endpoints at different post-irradiation times: clonogenic survival after ~ 2 weeks; cell cycle distribution, cell death, frequency of micronucleated cells and atypical mitoses, activation of matrix metalloproteases (MMPs) and of different proteins involved in DNA damage response and cell-cycle regulation at earlier time-points, up to 48 hours post-exposure. Combined techniques of flow-cytometry, immunofluorescence microscopy, gelatin zymography and western blotting were used. For selected endpoints, we also addressed the impact of the irradiation protocol, comparing results obtained when cells are plated before irradiation or first-irradiated and then re-plated. Caco-2 resistance to radiation, previously assessed up to 72 hours post exposure in terms of cell viability, does not translate into a high clonogenic survival. Survival is not affected by the irradiation protocol, while endpoints measured on a shorter time frame are. Radiation mainly induces a G2-phase arrest, confirmed by associated molecular markers. The activation of death pathways is dose- and time-dependent, and correlates with a dose-dependent inhibition of MMPs. Genomic instability markers are also found to be dose-dependent. The phosphorylated forms of several proteins involved in cell-cycle regulation increase following exposure; the key regulator FoxM1 appears to be downregulated, also leading to inhibition of MMP-2. A unified molecular model of the chain of events initiated by radiation is proposed to interpret all experimental results.